PROTOTYPING OF MICROWAVE DEVICES WITH SPECIFIED ELECTRODYNAMIC CHARACTERISTICS USING ADDITIVE 3D PRINTING TECHNOLOGY - S. V. Kharalgin; G. V. Kulikov; A. B. Kotelnikov; M. V. Snastin; E. M. Dobychina (Российский технологический журнал)
The technology of additive 3D printing is widely used in various branches of science and industry. The purpose of the research presented in the article is to evaluate and study the possibilities of 3D printing technology applied to the manufacture of microwave devices and to compare the characteristics of the devices obtained with the characteristics used in the electrodynamic model. Printing metal parts is an overly expensive process in small-scale production, both in terms of the cost of equipment and in relation to the materials used. In this work, parts for microwave devices were made of plastic with the aim of cheapening. Relatively cheap polymers used in 3D printing are dielectrics. Therefore, to limit the propagation of an electromagnetic wave in all directions it was necessary to create a conductive layer on the surface of printed models. The article: identifies the FFF print parameters that affect to the maximum extent the propagation of an electromagnetic wave; describes the process and problems encountered when printing and galvanizing parts; discusses the steps of modeling devices and measuring their parameters. The characteristics of microwave devices made by 3D printing technology were investigated. An assessment of the possibilities of manufacturing antennas and coaxial-waveguide transitions using this technology was carried out. To implement the conductive layer on the surface of the models, the method of galvanization was used. The adhesion properties of the obtained metallic coatings were investigated. The results of electromagnetic modeling are given. The parameters that affect to the maximum extent the quality of the implemented devices were determined. Laboratory measurements of the characteristics of produced devices were conducted. The simulation results of the examined devices are in good agreement with the experimental characteristics of the made models using 3D printing technology. A complete production cycle of microwave devices was carried out: design, simulation, sample production, and validation of characteristics. Prospects for the further development of the described technology include a variation of the types of plastics used as a substrate, the application of finishing decorative and functional coatings, an improvement in the adhesion properties of the applied copper layer with the substrate.